2022
DOI: 10.1002/oby.23330
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA panels predict bariatric surgery outcomes

Abstract: Objective:The weight losses after bariatric surgery are modulated by multiple factors in people with obesity. MicroRNAs (miRNAs) have been reported to show significant regulatory roles in adipose tissue. However, a serum miRNA signature to serve as a biomarker of sustained weight losses following bariatric surgery has not yet been established. Methods:MiRNA microarray was used to identify differentially expressed miRNAs in the serum of patients with an effective response after bariatric surgery compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Instead, Nunez identified the most influential miRNA 328-3p, 181a-5p, and 31-5p. Interestingly, 328-3p and 181a-5p miRNAs were only used in Nunez and Yeh et al [9,22] was not identified by other studies as the most pronounced, and 31-5p was in three studies, the most prominent [9,12,22]. Kuryłowicz et al found an effect whereby 122-5p was involved in inflammation and immune response with no further explanation [32].…”
Section: Mirna 122/122-5pmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, Nunez identified the most influential miRNA 328-3p, 181a-5p, and 31-5p. Interestingly, 328-3p and 181a-5p miRNAs were only used in Nunez and Yeh et al [9,22] was not identified by other studies as the most pronounced, and 31-5p was in three studies, the most prominent [9,12,22]. Kuryłowicz et al found an effect whereby 122-5p was involved in inflammation and immune response with no further explanation [32].…”
Section: Mirna 122/122-5pmentioning
confidence: 99%
“…In our analysis, miRNA 122 and 122-5p were mentioned the most in the reviewed studies. Specifically, miRNA 122 was mentioned in three distinct studies [4,19,26], while miRNA-122-5p was referenced in seven [9,13,16,17,22,25,32] Blum et al delved into the effects of MBS on vascular endothelial cells (VAC). Their research was geared towards understanding the potential role of MBS in preventing cancer and protecting VAC [26].…”
Section: Mirna 122/122-5pmentioning
confidence: 99%
See 1 more Smart Citation
“…The miR-31-5p was downregulated, while miR-328-3p and miR-181a-5p were upregulated in patients with a %EWL > 55% at 6 months after surgery, when compared with those that failed to achieve optimal weight reduction. Panels using the ratios of circulating miR-328-3p/miR-31-5p or miR-181a-5p/miR-31-5p showed a fair performance in the prediction of RYGB efficacy, with an AUC of 0.680 and 0.669, respectively [ 175 ].…”
Section: Predictors Of Success In Bariatric Surgerymentioning
confidence: 99%
“…Although metabolic surgery is common in developed countries, it has only started to gain recognition in Malaysia over the past few years. The serum miRNA biomarkers of sustained weight loss following metabolic surgery are not yet well-established [ 16 ]. It will be exciting to study these potential biomarkers in our population.…”
Section: Introductionmentioning
confidence: 99%